Impact of maternal antepartum depressive and anxiety symptoms on birth outcomes and mode of delivery: a prospective cohort study in east and west coasts of Malaysia - Hashima E. Nasreen; Hafizah Binti Pasi; Sakinah Md Rifin; Mohd Aznan Md Aris; Jamalludin Ab Rahman; Razman Mohd Rus; Maigun Edhborg (BMC, 2019)
Abstract Background Antepartum depressive and anxiety symptoms (ADS and AAS) are prevalent in Malaysia. Prior evidence linking maternal ADS and AAS with adverse birth outcomes and caesarean section (CS) or instrumental delivery is conflicting. There is no research in Malaysia on the association between maternal mental disorders and adverse birth outcomes and mode of delivery. This study aims to investigate the independent effect of maternal ADS and AAS on low birth weight (LBW), preterm birth (PTB) and CS or instrumental delivery among women in east and west coasts of Malaysia. Methods We used data from a prospective cohort study of 799 pregnant women from health clinics of two states in east and west coasts of Malaysia. Baseline data were measured at the third trimester of pregnancy on ADS, AAS, socioeconomic condition, anthropometric status, reproductive history and intimate partner violence. Birth outcomes and mode of delivery were determined at the time of delivery. Univariate and multiple Cox's regressions were applied to assess the association between ADS and AAS and LBW, PTB and CS or instrumental delivery. Results ADS was significantly associated with an increased risk of giving birth to LBW babies in both east coast (RR = 3.64; 95% CI 1.79-7.40) and west coast (RR = 3.82; 95% CI 1.86-7.84), but not with PTB. AAS was associated with increased risk of both LBW (RR = 2.47; 95% CI 1.39-4.38) and PTB (RR = 2.49; 95% CI 1.16-5.36) in the east coast, but not in west coast. The risk of CS or instrumental delivery was evident among women with ADS (RR = 2.44; 95% CI 1.48-4.03) in west coast only. Conclusion ADS predicts LBW in both coasts, AAS predicts LBW and PTB in east coast, and ADS predicts CS or instrumental delivery in west coast. Policies aimed at detection and management of ADS and AAS during antenatal check-up in health clinics may help improve birth outcomes and reduce obstetric interventions.